Evaluation of the efficiency of transportation network between urban centers of Sulaimani province A study in urban geography - اجمد, أمانج فؤاد أجماد; حسين, آ.د. بيان علي حسين (Sulaimani Journal for Humanities, 2025)
This study; is an attempt to analyze and evaluate the road network of Sulaimani province and their quantitative impact in determining the characteristics of the structure of the urban system It will describe the transportation routes in terms of connectivity, circulation level, ease of access and density, analyze the relationship between the length of the routes in the network and population distribution, and then present their impact on the urban system dimensions of the study area. The most important findings of the study are that the capacity of the transportation network is not at the required level, but the network has several positive points, especially in terms of connectivity and density of roads according to the variable area, because more than There is an interconnected network in the study area that connects all cities directly and indirectly.
Keywords: Urban system; Circuitry; Connectivity; Detour Index; Accessibility